All over the map - Fraser, Laura (Harmony Books, 2010)
Celebrating her fortieth birthday, Laura Fraser confronts the trajectory of her life. Divorced and childless in her thirties, she found solace in the wanderlust that had always directed her heart, but now she wonders if her passion for travel (and for short-lived romantic rendezvous) has deprived her of what she secretly wants most: a husband, a family, a home. How to reconcile what seem to be two opposite desires: for adventure, great food, and new experiences, but also a place to call home--and a loving pair of arms to greet her there? So, she globe hops. What else is a travel writer to do? She enjoys new cultures and local delicacies, always on the lookout for the "one." But a terrible incident suddenly makes her aware of her vulnerability, and she becomes afraid of traveling. Might she lose her greatest pleasure, not to mention her career?--From publisher description.